Awareness of age-related change in very different cultural-political contexts: A cross-cultural examination of aging in Burkina Faso and Germany - Schönstein, Anton; Schlomann, Anna; Wahl, Hans-Werner; Bärnighausen, Till (Frontiers in Psychiatry, 2023)
Combining recent developments in research on personal Views on Aging (VoA) and a cross-country comparative approach, this article examined Awareness of Age-related Change (AARC) in samples from rural Burkina Faso and from Germany. Research goals were (1) to examine for an assumed proportional shift in the relationship between gains/losses towards more losses as predicted by life-span psychology; (2) to estimate the association between AARC dimensions and subjective age; and (3) to examine the association between health variables and AARC. A cross-sectional method involving a large, representative sample from Burkina Faso that included participants aged 40 and older (N=3028) as well as a smaller convenience sample of German respondents aged 50 years and older (N=541) were used to address these questions. A proportional shift towards more AARC-losses was more clearly observable in the sample from Burkina Faso as compared to the German reference. Subjective age was in both samples consistently more strongly related to AARC-losses than to AARC-gains. Within the sample from Burkina Faso, differential associations of AARC-gains and AARC-losses to health variables could be shown. Concluding, findings support key tenets of life-span psychology including that age-related gains take place even late in life, but also that with increasing age a shift towards more losses takes place. Also, feeling subjectively younger may indeed be more strongly guided by lowered negative aging experiences than by increased positive ones.